Penerapan Digital Marketing Multichannel untuk Pemasaran Program Studi Sistem Informasi - Vania Valentina Pandora; Yenni M Djajalaksana (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
The digital era has driven the development of marketing at light speed. Conventional marketing has begun to transform into online marketing platforms or commonly referred to as digital marketing. An Information System Study Program at a Private University located in Bandung city, Indonesia implemented an increase the intensity of soft selling to potential new students by creating a landing page Belajarsisfo using components related to digital marketing. Belajarsisfo is a site for sharing knowledge and tips and tricks about the world of Information Technology. Belajarsisfo used soft selling sales techniques that were made with the main aim of getting leads for the Information Systems Study Program. An attempt to optimize the digital marketing efforts was to conduct multichannel digital marketing efforts through several platforms of Social Media, Website, Blog Site, and Email. The results of this research were evaluated using Google Analytics, Instagram Insight, Facebook Insight, Facebook Pixel, and Email Campaign Report to determine future adjustment to the target consumer and can produce measurable and accurate data.